Exploring the Impact of Artificial Intelligence on Women's Empowerment: A Comprehensive Survey - Shahbazi, Hafizullah; Hakimi, Musawer; Ulusi, Helena; Rahimi, Behnaz; Quraishi, Tamanna (Journal of Community Service and Society Empowerment, 2024)
Artificial intelligence (AI) has the capacity to greatly empower women and promote gender equality on a global scale. However, in order to effectively utilise AI to promote women's empowerment, it is crucial to have a comprehensive comprehension of its influence, possibilities, and difficulties. This study examines the various aspects of how AI contributes to the advancement of women's empowerment. It explores the extent to which AI is integrated into initiatives aimed at empowering women, the perceived impact of AI on women's empowerment on a global scale, and the obstacles women face in accessing AI opportunities. An integrated research methodology, including of surveys and literature evaluation, was utilised to collect data from a diverse sample of 88 people. The results indicate a substantial degree of AI incorporation in projects aimed at empowering women, with varying perspectives on the impact of AI. Additionally, the study revealed difficulties in accessing AI opportunities and observed differing levels of knowledge among women. This study highlights the significance of ethical issues and inclusive policies in utilising AI to promote women's empowerment. The findings provide significant knowledge for policymakers, researchers, and practitioners who aim to utilise AI's revolutionary capacity to promote gender equality and empower women on a global scale.